Tantangan Pengembangan Jaringan Pasokan Global Bagi Usaha Kecil, Mikro Dan Menengah (UMKM) - Tri Nanda Rayani Sinuhaji; Hendra Ibrahim (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This journal analyzes the challenges faced by Small, Micro and Medium Enterprises (MSMEs) in developing global supply networks. In an era of increasingly connected globalization, MSMEs have great potential to access global markets, however, they also face a number of complex obstacles. The main challenges discussed in this journal include limited resources and capital which limit the ability of MSMEs to compete in a competitive global market. . In addition, differences in international trade policies, regulations, and compliance with international standards are crucial factors that influence the global supply network of MSMEs. Developing a global supply network has become a priority for Small, Micro, and Medium Enterprises (MSMEs) in facing challenges in increasing their presence in an increasingly connected global market. However, MSMEs often face a number of significant obstacles in their efforts to develop global supply networks. This article investigates the key challenges faced by MSMEs in the context of developing global supply networks, focusing on aspects such as limited financial resources, regulatory complexity and technological limitations. Through a synthesis of financial management, supply chain, entrepreneurship, and international marketing theories, this article explores the impact of these challenges on the ability of MSMEs to develop their global supply networks.